Analysis Of Students' Difficulties In Learning Pronunciation Skill At Tenth Grade Of SMK Sore Tulungagung In Academic Year 2024/2025 - Muchamad Husein Fahrurizki; Moh. Choirul Huda (Journal Innovation In Education, 2025)
The study was conducted based on the observation that many students face challenges in pronouncing English words correctly, which hindered their speaking fluency and lowered their self-confidence in English communication. The study sought to identify specific pronunciation problems and explore the underlying causes of those difficulties. This research method used a qualitative descriptive approach. The subjects of this this study were by tenth-grade students of SMK Sore Tulungagung in the 2024/2025 academic year with a total of 10 students. The data were collected through classroom observation, open-ended questionnaires and semi-structured interviews. The findings revealed four major categories of pronunciation difficulties : phonetic differences (90%), lack of opportunity to practice (70%), low self-confidence (60%), and an unsupportive classroom atmosphere (40%). Data were analyzed through three steps : data reduction, data display and conclusion drawing, where the researcher interpreted the findings. It is suggested that teacher should incorporate pronunciation-focused strategies such as modeling, repetition drills, and immediate corrective feedback. Students are encouraged to actively practice pronunciation both inside and outside the classroom. For further studies may explore ppronunciation challenges in larger or more diverse student populations the effectiveness of specific intervention techniques such as mobile-assisted pronounciation tools. In addition, the study emphasizes the importance of creating a more supportive and interactive learning environment that fosters student confidence in speaking. Teachers can play a crucial role in reducing anxiety by providing a safe space for students to practice without fear of judgment. Collaborative activities such as peer-to-peer pronunciation exercises and pronunciation games could also help students gain more exposure to correct pronunciation in a less formal setting. Furthermore, integrating technology such as pronunciation apps or online platforms may allow students to practice at their own pace, enhancing their learning experience and improving their confidence in speaking English.